Examining the public sector recruitment and selection, in relation to job analysis in Pakistan - Ashraf, Junaid (Cogent social sciences, 2017)
The purpose of this research was to study the recruitment and selection practices in public sector of Pakistan with respect to job analysis. Job analysis is the most essential part of human resource activities. This research tries to study whether job analysis practices are followed or not. The research obtained information from 144 respondents, through questionnaires and some brief interviews. The primary and secondary data collected for the research concludes that the hiring process of public sector is flawed mainly because of poor job analysis. They do not make proper job descriptions and employees tasks do not match with the given job description, which ultimately effects the performance of the public sector organizations in Pakistan.